Entrepreneurial Character Formation at Al-Firdausiy Islamic Boarding School, Semarang City - Nur Ismianah; Dwi Istiyani; Nasirudin (GURUPEDIA: Journal of Teacher and Education, 2026)
This study analyzes the strategies for developing entrepreneurial character at the Al-Firdausiy Islamic Boarding School in Semarang. Using a qualitative approach with a phenomenological design, data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results indicate that the development of students' entrepreneurial character is carried out through three main strategies: (1) cognitive development through the study of classical texts such as Fathul Qorib and Bulughul Marom, as well as training in basic entrepreneurial theory, including profit calculation, risk mitigation, and market price analysis; (2) the development of entrepreneurial attitudes and principles through the Semarang Ngajiyuk Institute program and the character-based Islamic boarding school; (3) the development of behavior through direct practice, such as selling activities on campus. Entrepreneurial character is a key program of the Islamic boarding school, with the vision of "good morals, good at reciting the Quran, and good at trading." This program has resulted in students becoming independent, disciplined, creative, and responsible.